2013
DOI: 10.1038/mt.2013.110
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effects of Chimeric Receptor Engineered Human T Cells Directed to Tumor Stroma

Abstract: Cancer-associated fibroblasts (CAFs), the principle component of the tumor-associated stroma, form a highly protumorigenic and immunosuppressive microenvironment that mediates therapeutic resistance. Co-targeting CAFs in addition to cancer cells may therefore augment the antitumor response. Fibroblast activation protein-α (FAP), a type 2 dipeptidyl peptidase, is expressed on CAFs in a majority of solid tumors making it an attractive immunotherapeutic target. To target FAP-positive CAFs in the tumor-associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
247
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(254 citation statements)
references
References 44 publications
7
247
0
Order By: Relevance
“…Reports demonstrating that FAP can regulate PTEN/PI3K/AKT and Ras/ERK signaling pathways to enhance tumor cells undergoing EMT, migration, invasion, and metastasis support this hypothesis (7,14). Upregulation of FAP in PDA cells undergoing EMT may offer an opportunity to target these cells therapeutically with chimeric antigen receptor T cells as previously reported (23,(28)(29)(30)(31). Careful examination and dissection of the antitumor effect achieved by targeting FAP + stromal cells and/or FAP + EMT tumor cells would be critical in future studies.…”
Section: Discussionmentioning
confidence: 60%
“…Reports demonstrating that FAP can regulate PTEN/PI3K/AKT and Ras/ERK signaling pathways to enhance tumor cells undergoing EMT, migration, invasion, and metastasis support this hypothesis (7,14). Upregulation of FAP in PDA cells undergoing EMT may offer an opportunity to target these cells therapeutically with chimeric antigen receptor T cells as previously reported (23,(28)(29)(30)(31). Careful examination and dissection of the antitumor effect achieved by targeting FAP + stromal cells and/or FAP + EMT tumor cells would be critical in future studies.…”
Section: Discussionmentioning
confidence: 60%
“…37, 38 The use of these few non-cancer-specific antigens, which include FAP, 39 EGFR, 40 mesothelin 41 and glypican-3, 17 has led to poor or undefined therapeutic outcomes in patients. It is therefore important to broaden the NSCLC-specific targets of CAR T cells.…”
Section: Discussionmentioning
confidence: 99%
“…The stroma is composed of heterogeneous cell types including tumor fibroblasts, connective tissue cells, vascular endothelial cells, and immune subtypes such as lymphocytes, granulocytes, and macrophages. Kakarla et al and Wang et al have consistently reported that inhibiting tumor growth by targeting tumor stroma with CAR-T cells directed to fibroblast activation protein (FAP) can be safe and effective (Kakarla et al, 2013;Wang et al, 2014). Targeting tumor vasculature provides another means for therapy against multiple solid tumor types.…”
Section: Selecting Tumor Antigensmentioning
confidence: 99%